1999
DOI: 10.1139/z99-160
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of high-elevation lakes by long-toed salamanders (Ambystoma macrodactylum) after the extinction of introduced trout populations

Abstract: We surveyed high-elevation lakes for long-toed salamander (Ambystoma macrodactylum) larvae and trout in the northern Bitterroot Mountains of Montana, U.S.A., in 1978Montana, U.S.A., in , 1997Montana, U.S.A., in , and 1998. Our objectives were to (i) test whether trout exclude salamander populations; (ii) determine whether lakes in which trout have gone extinct have since been colonized by salamanders; and (iii) estimate the rates of population extinction and colonization in lakes never stocked with trout. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 39 publications
0
20
0
2
Order By: Relevance
“…The potential for successful management of non-native fishes in montane environments is a rare opportunity in national and international efforts to reverse or mitigate the effects of non-native species (Kats & Ferrer, 2003). Amphibian populations can recover if fish die out following cessation of stocking (Funk & Dunlap, 1999;Knapp et al, 2001Knapp et al, , 2005Eaton et al, 2005). Experiments in California have demonstrated that non-native fish can be successfully removed from water bodies 1-2 ha in size, and native amphibian populations begin to recover within 1-2 years after fish elimination (Vredenburg, 2004;Knapp et al, 2007;Pope, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The potential for successful management of non-native fishes in montane environments is a rare opportunity in national and international efforts to reverse or mitigate the effects of non-native species (Kats & Ferrer, 2003). Amphibian populations can recover if fish die out following cessation of stocking (Funk & Dunlap, 1999;Knapp et al, 2001Knapp et al, , 2005Eaton et al, 2005). Experiments in California have demonstrated that non-native fish can be successfully removed from water bodies 1-2 ha in size, and native amphibian populations begin to recover within 1-2 years after fish elimination (Vredenburg, 2004;Knapp et al, 2007;Pope, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These introductions resulted in dramatic changes to the distribution of many native aquatic species (Anderson, 1980;Stoddard, 1987;Bradford et al, 1998;Carlisle and Hawkins, 1998;Knapp et al, 2001), including amphibians (Tyler et al, 1998;Knapp and Matthews, 2000;Pilliod and Peterson, 2001;Knapp, 2005). The possibility that the negative effects of introduced fish on amphibians can be reversed was suggested by studies showing that amphibians often recovered following the termination of stocking and the subsequent disappearance of introduced fish populations (Funk and Dunlap, 1999;Knapp et al, 2001;Knapp et al, 2005). This apparent reversibility was recently confirmed for the mountain yellow-legged frog, Rana muscosa, through the use of a multi-lake fish removal experiment (Vredenburg, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Gambusia for mosquito control, accumulating evidence suggests that this small poeciliid fish is far from a panacea; due presumably to their generalist feeding habits (GarciaBerthou, 1999), they are not always effective at reducing mosquitoes (Hoy, Kauffman & O'Berg, 1972;Arthington & Lloyd, 1989;Blaustein, 1992) and they may negatively impact non-target organisms including endangered amphibian species, fishes and invertebrates (Courtenay & Meffe, 1989;Alcaraz, Bisazza & Garc´ıa-Berthou, 2008). In the case of amphibians, negative effects of Gambusia species (Gamradt & Kats, 1996;Goodsell & Kats, 1999;Lawler et al, 1999;Hamer, Lane & Mahony, 2002) and other fishes (Tyler et al, 1998;Funk & Dunlap, 1999;Hoffman, Larson & Samora, 2004;Denoel, Dzukic & Kalezic, 2005) have been documented on populations of a number of amphibian species. Most of these studies have considered anurans, and not urodeles, and even fewer studies have considered how mosquitofish in particular affect urodeles.…”
Section: Introductionmentioning
confidence: 99%